Stroke performance during a time limit test at vVO2max in elite swimmers - Marinho, D. A.; Vilas-Boas, J. P.; Keskinen, K. L.; Rodriguez, F. A.; Soares, S. M.; Carmo, C. M.; Vilar, S. O.; Fernandes, R. J. (First international symposium sciences and practices in swimming, 2006)
The aim of this study was to analyse the stroking parameters during a time limit test performed at the minimum velocity that elicits maximal oxygen uptake (TLim-vVO2max) in elite freestyle swimmers. Eleven swimmers from the National Portuguese Swimming Team (5 male and 6 female) performed an intermittent incremental test for vVO2max assessment and an all-out swim at vVO2max to determine TLim-vVO2max and to analyse the evolution of the stroking parameters throughout the test. Stroke rate increased and stroke length (and stroke index) decreased during the TLim-vVO2max test with significant changes (p < 0.05) at 25%, 50% and 87.5% of its duration. These data show a reduction of the propelling efficiency throughout such a test. These findings could be useful when designing training programs, namely of middle distance swimmers.